HUBUNGAN PERHATIAN ORANGTUA DENGAN MORAL REMAJA - Gianoza, Jaufani (Universitas Negeri Padang, 2013)
Family is the first environment encountered by children. One of the the phenomenons face in the family is the lack of parents attention to their children. Thus, in the everyday life, their behaviors are less accordance with norms and religious values. This study aimed to describe the attention of parents, moral of adolescents, and examine the relationship between them. The type of this study is a descriptive correlation with the findings of parents attention is high, while adolescent moral classified as poor, and there is a significant relationship between the attention of parrents to the moral of adolescents. Keywords: Parrents Attention; Adolescents Moral